The Presence of Functional Compounds of Moringa Leaf Powder (Moringa Oleifera) Due to Technical Handling and Drying Temperature: How it Affects Humans - Asep Dedy Sutrisno; Yusman Taufik (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Moringa (Moringa oleifera) is a plant that contains many functional compounds that are useful for supporting human health, especially for prevention and overcoming degenerative diseases due to the influence of unfavorable conditions and environment. The purpose of this study is to obtain facts and information about the degradation pattern of functional values of the compounds contained therein, namely vitamin C, β-carotene, and antioxidant activity after the drying process. While the aim is to optimize the handling and processing of Moringa leaves into powder to be more useful in preventing and overcoming certain diseases, so as to maintain human health. The research methodology that has been carried out includes preliminary research, namely analyzing or testing the content of vitamin C, β-carotene, and antioxidant activity in fresh Moringa leaves. The main research used a randomized block design (RBD) which consisted of two factors, namely treatment before drying (TBD) and drying temperature. The variable response was a decrease in the content of vitamin C, β-carotene, and antioxidant activity of Moringa leaf powder after drying. The results of the study the factors of treatment before drying (TBD) and drying temperature showed a significant effect on decreasing the content of vitamin C, β-carotene, and antioxidant activity. The higher the drying temperature the content of vitamin C, β-carotene, and antioxidant activity decreases. Processing of Moringa leaves into powder using the lowest possible drying temperature can reduce the reduction in the content of functional compounds.